Heteropolyacid supported on acidic clay: a novel efficient catalyst for alkylation of ethylbenzene with dilute ethanol to diethylbenzene in presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Journal of Molecular Catalysis A-Chemical, 2008)
Vapor phase alkylation of ethylbenzene with ethanol to diethylbenzene is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinyl benzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor phase alkylation of ethylbenzene with ethylene using zeolitic catalysts. The efficacy of dodecatungsotphosphoric acid (DTPA) supported on acid treated clay has been evaluated in the current work in the alkylation of ethylbenzene with 80% (w/w) ethanol. 15% (w/w) DTPA/K-10 clay was found to be an efficient and robust catalyst. The use of aqueous ethanol and a mixed C-8 stream lowers the cost of production. A kinetic model is developed by studying the important process parameters with 15% (w/w) DTPA/K-10 as the catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkylation; diethylbenzene; Heteropolyacid; kinetics; Solid acids